Beach and dune reinforcement with geotextile encapsulated-sand systems. The Portuguese experience - Luciana das Neves (2015)
Geotextile encapsulated-sand systems can provide efficient protection in eroding shorelines of invaluable landscape, and low to medium risk management. Over the last decade in Portugal, due to the perception that hard coastal interventions have functional limitations and generate negative impacts, new approaches are receiving increased attention from both, government agencies and stakeholders. The Portuguese experience with geosystems are summarised in the paper, along with the results from an ongoing RTD project that aims to develop a new technology of coastal protection incorporating geotextile encapsulated-sand systems, more suitable for applications under severe hydrodynamic conditions, notably similar to those occurring along the northwest Portuguese Atlantic coast.